1989
DOI: 10.1159/000138542
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Induced Thyroid Dysfunction upon Uterine Responsiveness in Strips from Pregnant and Nonpregnant Rats

Abstract: The influence of thyroid dysfunction on rat myometrial responsiveness to oxytocin, acetylcholine, CaCl2 and BaCl2 was assessed in uterine strips from pregnant and nonpregnant rats. In preparations obtained from hypothyroid nonpregnant rats, oxytocin and acetylcholine concentration-response curves were significantly displaced to the left, whereas myometrial strips from hyperthyroid nonpregnant rats were only supersensitive to acetylcholine. In relation to the pregnant state, T3 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…The TSH receptor (TSHR) is expressed not only in the thyroid, but also in adipose tissue, brain, orbital tissue, lymphocytes and bone. Only two studies were found, one showing reduced responsiveness to uterine agonists in hypothyroid rats, 22 and another concluding that this might be caused by a reduction in uterine myometrial Ca 2 + channel function. 21 However, until now, no TSHR has been described in the uterus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The TSH receptor (TSHR) is expressed not only in the thyroid, but also in adipose tissue, brain, orbital tissue, lymphocytes and bone. Only two studies were found, one showing reduced responsiveness to uterine agonists in hypothyroid rats, 22 and another concluding that this might be caused by a reduction in uterine myometrial Ca 2 + channel function. 21 However, until now, no TSHR has been described in the uterus.…”
Section: Discussionmentioning
confidence: 99%
“…Empirical evidence regarding such a direct effect is, however, scarce. Only two studies were found, one showing reduced responsiveness to uterine agonists in hypothyroid rats, 22 and another concluding that this might be caused by a reduction in uterine myometrial Ca 2 + channel function. 23 Uterine contractions are important for final cephalic presentation at term as has been suggested by a large Norwegian study including over 45,000 breech cases.…”
Section: Discussionmentioning
confidence: 99%
“…The existence of a large-conductance calcium-activated potassium channel (BK Ca ) is demonstrated in pregnant human myometrium and is even shown to be involved in uterine quiescence (2,17,22). A modification in BK Ca conductance is related to a change in the functionality of uterine contractile response (16,25).Several investigative groups have analyzed the effect of thyroid dysfunction on pregnant uterine tissue and in particular have observed an effect of low levels of T 4 on uterine contractile activities in gravid rats (24,30). Hypothyroidism has also been found to reduce calcium channel function in pregnant rat uterine tissue (30).…”
mentioning
confidence: 99%
“…Several investigative groups have analyzed the effect of thyroid dysfunction on pregnant uterine tissue and in particular have observed an effect of low levels of T 4 on uterine contractile activities in gravid rats (24,30). Hypothyroidism has also been found to reduce calcium channel function in pregnant rat uterine tissue (30).…”
mentioning
confidence: 99%
“…Moreover, thyroid hormones have been shown to influence calcium homeostasis and flux responsible for excitation and contractility, with T4 and T3 modulating its pharmacological control and secretion [8] . Therefore, uterine responsiveness to various uterotonic agents is significantly modified under thyroid disorders [9] , [10] .…”
Section: Introductionmentioning
confidence: 99%